Methylation of GPLs in Mycobacterium smegmatis and Mycobacterium avium - Jeevarajah, Dharshini; Patterson, John H; Taig, Ellen; Sargeant, Tobias; McConville, Malcolm J; Billman-Jacobe, Helen (Journal of bacteriology, 2004)
Several species of mycobacteria express abundant glycopeptidolipids (GPLs) on the surfaces of their cells. The GPLs are glycolipids that contain modified sugars including acetylated 6-deoxy-talose and methylated rhamnose. Four methyltransferases have been implicated in the synthesis of the GPLs of Mycobacterium smegmatis and Mycobacterium avium. A rhamnosyl 3-O-methytransferase and a fatty acid methyltransferase of M. smegmatis have been previously characterized. In this paper, we characterize the methyltransferases that are responsible for modifying the hydroxyl groups at positions 2 and 4 of rhamnose and propose the biosynthetic sequence of GPL trimethylrhamnose formation. The analysis of M. avium genes through the creation of specific mutants is technically difficult; therefore, an alternative approach to determine the function of putative methyltransferases of M. avium was undertaken. Complementation of M. smegmatis methyltransferase mutants with M. avium genes revealed that MtfC and MtfB of the latter species have 4-O-methyltransferase activity and that MtfD is a 3-O-methyltransferase which can modify rhamnose of GPLs in M. smegmatis.